PENGEMBANGAN MEDIA PEMBELAJARAN KONTRUKSI RODA DAN BAN BERBASIS APLIKASI ANDROID DI SMK NEGERI 1 TENGARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Rohmana, Deka; Suwahyo, Suwahyo (Automotive Science and Education Journal, 2020)
The purpose of this study was to develop learning media based on android applications on wheel and tire construction materials to determine the improvement of learning outcomes at SMK Negeri 1 Tengaran. The feasibility of learning media and student responses to the media developed. The development model in this study uses the ADDIE model. Based on the research results, the increase in the pretest-posttest average score was 18.89. T-test value tcount (6.00)> ttable (2.045). The increase in student learning outcomes obtained an average N-Gain test of 0.44 with moderate improvement criteria. Based on the results of the product feasibility test, the percentage of 83% for media experts and 85% for material experts was obtained, so that the Android application-based learning media met the very feasible category. Analysis of student responses obtained by 76% is in the very good category.